Experiences of pregnancy for women living with inflammatory bowel disease: a systematic review. (2nd October 2022) - Janiszewski, Helen; Radford, Shellie; Coad, Jane; Cooper, Joanne; Moran, Gordon; Greenaway, Claire; Bailey, Elizabeth
Abstract : Background: While women living with inflammatory bowel disease (IBD) have a similar fertility rate to the general population, they are at increased risk of pregnancy complications, and they are considered to have high-risk pregnancies requiring multidisciplinary care. Aims: A systematic literature review was conducted to investigate the experiences of pregnancy among women with IBD. Methods: The search terms ulcerative colitis, Crohn's disease, inflammatory bowel disease, IBD, antenatal care, pregnancy, experience, perception and perspectives (and combinations of these words using Boolean operators) were entered into the selected electronic databases. Findings: Of 1197 articles retrieved, 42 were full-text screened. Five articles were included, with data extraction by two independent reviewers. Five key themes were generated: timing of diagnosis; translation of healthcare practitioner knowledge of IBD and pregnancy into meaningful information; perceptions about IBD medication; impact of disease activity; and concerns about IBD and pregnancy. Conclusion: Insight into what shaped experiences of pregnancy was gained, with the small numbers of studies also highlighting the lack of research in this area. Further research in this area is recommended.